2022
DOI: 10.1021/acs.iecr.2c01179
|View full text |Cite
|
Sign up to set email alerts
|

Spherulitic Growth Strategy for Agitation-Induced Formation of Spherical Amoxicillin Sodium Products

Abstract: In industrial crystallization, spherical crystals have gained increasing interest due to their excellent physicochemical properties, such as high bulk density, flowability, stability, etc. However, their formation mechanism is still not well understood and is often oversimplified. In this work, spherical amoxicillin sodium crystals were obtained via a spherulitic growth strategy. It was found that agitation immediately after the addition of crystal seeds was critical for inducing radial noncrystallographic bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…It is well-known that high supersaturation is favorable to polycrystalline growth, and hence leads to the formation of spherulites. ,,, This can be attributed to dynamic heterogeneities: short induction period and high level of supersaturation lead to quick nucleation and growth rates faster than mixing. Furthermore, denser spherulites are more probable to form under higher supersaturation, as evidenced by the studies in the literature. ,, While Cui et al indicated that high supersaturation level may not be necessary for spherulitic growth. Crystallization substrates with enough defects and dislocations, such as crystal seeds with rough surfaces, could also induce non-crystallographic branching and spherulitic growth through the static heterogeneity mechanism, which aligns with the sentiment expressed in the literature …”
Section: Spherical Crystallization Technologies For Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well-known that high supersaturation is favorable to polycrystalline growth, and hence leads to the formation of spherulites. ,,, This can be attributed to dynamic heterogeneities: short induction period and high level of supersaturation lead to quick nucleation and growth rates faster than mixing. Furthermore, denser spherulites are more probable to form under higher supersaturation, as evidenced by the studies in the literature. ,, While Cui et al indicated that high supersaturation level may not be necessary for spherulitic growth. Crystallization substrates with enough defects and dislocations, such as crystal seeds with rough surfaces, could also induce non-crystallographic branching and spherulitic growth through the static heterogeneity mechanism, which aligns with the sentiment expressed in the literature …”
Section: Spherical Crystallization Technologies For Drugsmentioning
confidence: 99%
“…(e) The substrate-assisted SG mechanism. Reproduced from ref . Copyright 2022 American Chemical Society.…”
Section: Mechanisms and Design Principlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Spherical crystallization is an efficient technology that couples the crystallization and granulation processes, which is widely used in the pharmaceutical industry. The application of the spherical crystallization technique allows the elimination of the downstream particle property via improving the tabletability and enhancing unit operations such as milling, grinding, prilling, and so forth. Spherical or sphere-like drug particles prepared via the spherical crystallization technique can be directly used for tablet compression with improved flow properties, mechanical properties, drug solubility and bioavailability,etc. …”
Section: Introductionmentioning
confidence: 99%